Neurometabolic therapy in chronic cerebral ischemia - E. Yu. Solovyeva; M. V. Chirkova; V. D. Kovalev (Лечащий Врач, 2025)
Background. On February 10-12, 2025, the XXI Interdisciplinary Congress with international participation "Vein Readings" was held in Moscow. The congress is devoted to topical issues of neurology and every year successfully brings together leading specialists and scientists from near and far abroad. Created by the students of the legendary academician Alexander Vein (1928-2003), the congress not only fulfills the task of increasing the level of knowledge and professionalism of doctors, but also creates conditions for fruitful discussions and interdisciplinary dialog. Each "Vein Readings" is a large-scale event, causing increased attention of specialists. Participants share their own experience, the latest research, discoveries and developments. There are thematic trainings, symposia, discussions and clinical cases, as well as lectures by experts.Results. On the first day of the congress Ella Yu. Solovyeva, Doctor of Medical Sciences, Professor, Head of the Department of Neurology, Head of the Research Laboratory of Biomedical Research in Neurology, N. I. Pirogov Russian National Research Medical University (Moscow) gave a lecture "Problems and Opportunities of Neurometabolic Therapy", highlighting approaches to the prescription of neurometabolic drugs in clinical practice.